2014
DOI: 10.1002/2014gl060707
|View full text |Cite
|
Sign up to set email alerts
|

New evidence for generation mechanisms of discrete and hiss‐like whistler mode waves

Abstract: Linear theory suggests that whistler mode wave growth rates are proportional to the ratio of hot electron (~1 to 30 keV) density to total electron density (N h /N t ), whereas nonlinear wave theory suggests that an optimum linear growth rate is required to generate rising tone chorus from hiss-like emissions. Using the Time History of Events and Macroscale Interactions during Substorms waveform data collected by three probes over the past~5 years, we investigate the correlation between N h /N t and wave amplit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
103
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(113 citation statements)
references
References 55 publications
(81 reference statements)
10
103
0
Order By: Relevance
“…Broadband waves are mostly seen for larger density ratios, n b /n 0 > 1%, at this ratio of ω pe /Ω e = 3.2. Similar trends were observed for chorus and hiss in space [22].…”
Section: Lapdsupporting
confidence: 82%
See 1 more Smart Citation
“…Broadband waves are mostly seen for larger density ratios, n b /n 0 > 1%, at this ratio of ω pe /Ω e = 3.2. Similar trends were observed for chorus and hiss in space [22].…”
Section: Lapdsupporting
confidence: 82%
“…Plasma parameters in the laboratory and in the magnetosphere, plasma density [20], magnetic field strength, ratio of plasma frequency to cyclotron frequency [21], ratio of beam density to plasma density [22], ratio of whistler wave amplitude to background magnetic field strength [21,22], ratio of electron thermal pressure to magnetic pressure. beam source assembly.…”
Section: Lapdmentioning
confidence: 99%
“…They further successfully reproduced parallel propagating lower band rising tones with a 1‐D PIC (Particle In Cell) simulation model. Moreover, this theory also indicates that chorus waves should be excited under some optimum condition [ Hikishima and Omura , ], which was supported by the THEMIS observations [ Gao et al , ]. For upper band chorus waves, many potential mechanisms have been proposed to explain their generation and also the power gap at about 0.5 f ce , such as a strong damping at about 0.5 f ce [ Omura et al , ], different free energy sources [ Fu et al , ], and the lower band cascade [ Gao et al , ].…”
Section: Introductionmentioning
confidence: 80%
“…Chorus waves are typically detected in the vicinity of the magnetic equator (|MLAT| < 10°, where MLAT is the magnetic latitude) [ LeDocq et al , ; Santolik et al , ; Li et al , ], which has been recognized as their main source region. It has been widely accepted that chorus waves are excited through linear and nonlinear resonant interactions with hot and anisotropic electrons (tens of keV) injected from the plasma sheet during substorms [ Nunn , ; Karpman et al , ; Omura et al , , ; Shklyar and Matsumoto , ; Li et al , ; Demekhov , ; Omura and Nunn , ; Nunn and Omura , ; Gao et al , ; Nunn and Omura , ]. By considering the relativistic second‐order resonant condition, Omura et al [] found that the evolution of wave frequencies and amplitudes of chorus waves is controlled by the nonlinear resonant current resulting from resonant electron trapping into the effective potential generated by the wave electric field and the mirror force acting together on particles in the inhomogeneous geomagnetic field [see Trakhtengerts et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…For the case of strictly parallel propagating whistler waves (θ = 0), eqs. (1) and (2) can be solved for the frequency of the excited whistler wavē Plasma parameters in the laboratory and in the magnetosphere, plasma density [16], magnetic field strength, ratio of plasma frequency to cyclotron frequency [17], ratio of beam density to plasma density [18], ratio of whistler wave amplitude to background magnetic field strength [18,17], ratio of electron thermal pressure to magnetic pressure.…”
Section: Introductionmentioning
confidence: 99%